A study of the propensity for communicative aggressiveness in cadet pilots - M. V. Erkhova; I. Sh. Aizatullova (Вестник университета)
The article presents a model of personal resource of a civil aviation pilot and the experience of studying one of the components of this model – a communicative resource. The article analyses the results of a study of the propensity for communicative aggressiveness of the 5th year cadets of the Ulyanovsk Institute of Civil Aviation named after the Chief Marshal of Aviation B.P. Bugaev who are studying in the field of “Organization of flight work”. 83 people participated in the study. V.V. Bojko’s questionnaire “Determination of integral forms of communicative aggressiveness” was used as a diagnostic tool. This technique is designed to assess a person’s predisposition to aggression in various situations and contains 11 parameters of explicit and hidden forms of aggressive human behaviour. The article substantiates the relevance of studying communicative aggressiveness as a professional destruction of civil aviation pilots. The analysis of the average group and personal values of various parameters characterising the respondents’ propensity to aggressive manifestations was conducted. Recommendations are given on the development of emotional intelligence of future civil aviation pilots in the conditions of their higher professional education. The experience of the Ulyanovsk Institute of Civil Aviation in the prevention and correction of educational and professional stress of participants in the educational process is presented.